2016
DOI: 10.1590/s1679-87592016098506401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of the OC5 algorithm of IFREMER for the highly turbid waters of Río de la Plata

Abstract: Remote sensing provides a global vision of the oceans; validation is, however, an essential previous step. IFREMER developed the empirical algorithm OC5 for highly turbid (or type 2) waters and it performed well for the northwestern European shelf. The aim of this study was to evaluate the performance of this algorithm for the Río de la Plata estuary, utilizing in situ observations of chlorophyll-a and suspended matter. Our results show a low point-to-point correlation between in situ and remote observations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Los valores de concentración del MPS obtenidos por Moreira et al (2013) podrían estar subestimados, ya que los rangos de concentración del MPS con los que se generó el OC5 (Golfo de Biscay, Francia, IFEREMER) fueron valores mucho más bajos que los registrados para el estuario del RdlP . Además, la baja eficacia del OC5 en el RdlP también se debió al uso de correcciones atmosféricas estándar de la NASA, como así también a la naturaleza semi-empírica del algoritmo sensible a los cambios en la composición del agua y, por lo tanto, de validez regional Camiolo et al, 2016).…”
Section: Discussionunclassified
“…Los valores de concentración del MPS obtenidos por Moreira et al (2013) podrían estar subestimados, ya que los rangos de concentración del MPS con los que se generó el OC5 (Golfo de Biscay, Francia, IFEREMER) fueron valores mucho más bajos que los registrados para el estuario del RdlP . Además, la baja eficacia del OC5 en el RdlP también se debió al uso de correcciones atmosféricas estándar de la NASA, como así también a la naturaleza semi-empírica del algoritmo sensible a los cambios en la composición del agua y, por lo tanto, de validez regional Camiolo et al, 2016).…”
Section: Discussionunclassified
“…In a previous study the SPM distribution in the RdlP derived from MODIS-Aqua images using the OC5 empiric algorithm was analysed (Moreira et al 2013). The OC5 algorithm developed by IFREMER for the Bay of Biscay (Gohin et al 2002(Gohin et al , 2005 showed a poor performance in the turbid waters of the RdlP estuarine region (Camiolo et al 2016). The poor efficiency is mainly associated with the use of NASA standard atmospheric correction and with the semiempirical nature of the proposed algorithm, which could be sensitive to changes in water composition and would therefore only have regional validity (Camiolo et al 2016, Dogliotti et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The OC5 algorithm developed by IFREMER for the Bay of Biscay (Gohin et al 2002(Gohin et al , 2005 showed a poor performance in the turbid waters of the RdlP estuarine region (Camiolo et al 2016). The poor efficiency is mainly associated with the use of NASA standard atmospheric correction and with the semiempirical nature of the proposed algorithm, which could be sensitive to changes in water composition and would therefore only have regional validity (Camiolo et al 2016, Dogliotti et al 2016. It has been previously shown that the standard atmospheric correction completely fails to retrieve water reflectance in most of the RdlP's turbid waters, mainly due to sensor saturation in the bands 667, 748 and 869 nm used for the atmospheric correction and to incorrect estimation of the marine contribution in the near infrared in these extremely turbid waters (Dogliotti et al 2011).…”
Section: Introductionmentioning
confidence: 99%